The impact of the Syrian conflict on archaeological sites in Al-Hasakah province. (June 2022) - Mamo, Adnan Rashid; Ibraheem, Ismael M.; Al Kassem, Amal; Al-Khalil, Ahmed; Hopper, Kristen
Highlights: Damage estimation of 340 archaeological sites in Syria using satellite imagery. Analysis of remote sensing is consistent with the evidence reported from field visits. Looting and military damages have had a significant impact on archaeological sites. Valuable information on the condition of the sites through time was acquired. Abstract: This article assesses the impact of the Syrian conflict on archaeological sites in Al-Hasakah Governorate through a detailed analysis of satellite images. In total, the condition of 340 archaeological sites were examined on satellite images taken between 2004 and 2020. This has allowed us to assess when damage is likely to have occurred; in particular, which damage types have increased in frequency during the current conflict. We have compared these results to previously published information from satellite imagery assessments and field visits by local authorities. The results are consistent with the previous information in terms of damaged sites and types of damage. However, the current study presents a more comprehensive assessment of the timing of damage specific to Al-Hasakah region.